2017
DOI: 10.1002/esp.4256
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting lake sediment budgets: How the calculation of lake lifetime is strongly data and method dependent

Abstract: Lake sedimentation has a fundamental impact on lake lifetime. In this paper, we show how sensitive calculation of the latter is to the quality of data available and assumptions made during analysis. Based on the collection of a large new dataset, we quantify the sediment masses (1) mobilized on the hillslopes draining towards Lake Tana (Ethiopia), (2) stored in the floodplains, (3) transported into the lake, (4) deposited in the lake and (5) delivered out from the lake so as to establish a sediment budget. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 76 publications
8
37
1
Order By: Relevance
“…Like the rainfall pattern in LTB, this severe rate of sediment delivery to main rivers also follows an increasing trend from north to south in clockwise direction, that is, SY in subbasins located in Megech catchment (57 Mg ha −1 yr −1 ) is lower than subbasins located in north‐east (65 Mg ha −1 yr −1 ), Gumara (73 Mg ha −1 yr −1 ), and Gilgel Abay (80 Mg ha −1 yr −1 ) catchments. This estimated SY in this study is within the range reported data that were observed in and around LTB (Ayele et al, ; Ebabu et al, ; Lemma et al, ; Melaku et al, ; Subhatu et al, ). In contrasts, relatively lower sediment is produced in the low‐lying floodplains of the basin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Like the rainfall pattern in LTB, this severe rate of sediment delivery to main rivers also follows an increasing trend from north to south in clockwise direction, that is, SY in subbasins located in Megech catchment (57 Mg ha −1 yr −1 ) is lower than subbasins located in north‐east (65 Mg ha −1 yr −1 ), Gumara (73 Mg ha −1 yr −1 ), and Gilgel Abay (80 Mg ha −1 yr −1 ) catchments. This estimated SY in this study is within the range reported data that were observed in and around LTB (Ayele et al, ; Ebabu et al, ; Lemma et al, ; Melaku et al, ; Subhatu et al, ). In contrasts, relatively lower sediment is produced in the low‐lying floodplains of the basin.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 3,855 suspended sediment concentration (SSC) and its corresponding streamflow data were measured in the monitoring stations in Megech, Gumara, Gelda, and Gilgel Abay rivers (2012–2016). The average SSC is 3.51 ± 6.25 g L −1 that ranges from 2.50 (±4.95) in Gelda to 4.43 (±9.63) g L −1 in Megech, which is quite within the range of values reported by Lemma et al () and Ebabu et al () in LTB. The SSC in Megech River is a bit higher than the natural condition due to intensive river bank excavation for dam construction.…”
Section: Discussionsupporting
confidence: 85%
“…This value is a similar order of magnitude to the sediment delivered by other watersheds in the Ethiopian highlands (Abate et al, 2017;Dagnew et al, 2015;Tilahun et al, 2013aTilahun et al, , 2015Vanmaercke et al, 2010). Finally, the soil losses reported by Erkossa et al (2015) and Lemma et al (2017), with 2.7 t/ha/yr, are unrealistically low. Based on the average reported sediment concentration of 4.4 g/l in Lemma et al (2017), it can be easily shown that their sediment losses should agree with our calculations of around 30 t/ha/yr.…”
Section: Sediment Contributions To Lake Tanasupporting
confidence: 56%
“…Finally, the soil losses reported by Erkossa et al (2015) and Lemma et al (2017), with 2.7 t/ha/yr, are unrealistically low. Based on the average reported sediment concentration of 4.4 g/l in Lemma et al (2017), it can be easily shown that their sediment losses should agree with our calculations of around 30 t/ha/yr.…”
Section: Sediment Contributions To Lake Tanamentioning
confidence: 85%
“…The findings on cropland are also higher than the median of the measured values in Africa for catchments of 2 ha (7.8 Mg ha −1 yr −1 ) or 8 ha (6.3 Mg ha −1 yr −1 ; Vanmaercke et al, ). In Ethiopia, all measured SSY for catchments up to 1,000 km 2 are situated in the range of 5–40 Mg ha −1 yr −1 (Vanmaercke et al, : Lemma et al, ). Despite the higher rainfall than on all other measurement sites, the 2‐year measurement results on cropland lie well within this range.…”
Section: Discussionmentioning
confidence: 99%